THU0557 Low-Frequency Pulsed Electromagnetic Field Therapy for Non-Specific Neck Pain. (23rd January 2014) - Kocic, M. N.; Stankovic, A.; Krstovic, A.; Zivkovic, V.; Spalevic, M.; Dimitrijevic, L.
Abstract : Background: There are several types and causes of neck pain. Non-specific neck pain is the most common type. In most of the cases an underlying pathology cannot be definitively determined. It is important to start treatment as early as possible to prevent pain becoming chronic, which happens in more than 10% of patients with such pathology. Treatment is conservative. Medicaments, physical therapy, acupuncture and spinal manipulation is used. In spite of high prevalence there have been noted no conclusive evidence favoring one specific intervention over another in the conservative treatment of this pathology in literature on this subject. Objectives: The objective of this study was examining the effect of low-frequency pulsed electromagnetic field (PEMF) in patients with subacute non-specific neck pain. Methods: The study included 40 patients with nonspecific neck pain, which lasted from a month to three months. The excluding criteria are: presence of radiculopathy, mielopathy, vegetative symptoms, head and neck trauma, specific diagnosis (inflammatory, infectious, neoplastic diseases), patients younger than 18 and older than 65 years, pain intensity less than 30 mm on visual analog scale (VAS) (0-100mm). All patients were randomly allocated to two groups with 20 in each. All patients in both groups received 10 days of medicament therapy: nonsteroidal anti-inflammatory drugs (NSAIDs) and muscle relaxant. Treatment in group A was subsequently included PEMF (5MT, 25 Hz, 15 min, concentric coil) for a period of 4 weeks in combination with the exercises, while group B for 4 weeks had only exercises. In both groups of patients there were already individually measured: strengthening isometric exercises, isotonic to increase flexibility and range of motion, pain free range of motion. Patients were not allowed to use acetaminophen or NSAIDs, or muscle relaxant during these 4 weeks. The outcome assessment was performed before treatment and after treatment using 0-100mm VAS for pain evaluation. Results: Group A included 15 women and 5 men with a mean age of 47.78 ± 6.56. Group B included 13 women and 7 men, with a mean age of 49.19 ± 7.47 Pain was reduced in group A from 51.45 ± 0.86 (range: from 39mm to 62mm) to 21.10 ±1.12) (range: from10mm to 31mm) in Group B pain was reduced from 53.45 ± 1.18 (range from 34 mm to 71 mm) to 29.20 ± 1.10 (range: from 10 mm to 43mm). After the treatment pain was significantly reduced in both groups (p <0.001), but there were no statistically significant differences between groups (p> 0.05). Conclusions: In patients with subacute non-specific neck pain, exercises led to a statistically significant reduction in pain. Adding PEMF had no effect on pain reduction. References: Heintz MM, Hegedus EJ. Multimodal management of mechanical neck pain using a treatment based classification system. J Man Manip Ther. 2008; 16(4): 217–224. Disclosure of Interest: None Declared